A Systematic Literature Review of Students as Partners in Higher Education - Mercer-Mapstone, Lucy; Dvorakova, Sam Lucie; Matthews, Kelly E; Abbot, Sophia; Cheng, Breagh; Felten, Peter; Knorr, Kris; Marquis, Elizabeth; Shammas, Rafaella; Swaim, Kelly (International Journal for Students as Partners, 2017)
“Students as Partners” (SaP) in higher education re-envisions students and staff as active collaborators in teaching and learning. Understanding what research on partnership communicates across the literature is timely and relevant as more staff and students come to embrace SaP. Through a systematic literature review of empirical research, we explored the question: How are SaP practices in higher education presented in the academic literature? Trends across results provide insights into four themes: the importance of reciprocity in partnership; the need to make space in the literature for sharing the (equal) realities of partnership; a focus on partnership activities that are small scale, at the undergraduate level, extracurricular, and focused on teaching and learning enhancement; and the need to move toward inclusive, partnered learning communities in higher education. We highlight nine implications for future research and practice.